Assessment of Indoor & Outdoor Black Carbon emissions in rural areas of Indo-Gangetic Plain: seasonal characteristics, source apportionment and radiative forcing. (October 2018) - Arif, Mohammad; Kumar, Rajesh; Kumar, Ramesh; Zusman, Eric; Singh, Ramesh P.; Gupta, Akhilesh
Abstract: Black Carbon (BC) has been widely recognized as the second largest source of territorial and global climate change as well as a threat to human health. There has been serious concern of BC emission and its impact in Indo-Gangetic Plains (IGP) due to the use of biomass and fossil fuels for cooking, transportation and industrial activities. An attempt has been made to study indoor (Liquefied Petroleum Gas- LPG & Traditional cookstoves users households) and outdoor concentrations; seasonal characteristics; radiative forcing and source of apportionment of BC in three districts (Sitapur, Patna and Murshidabad) of IGP during January to December 2016. The seasonal concentrations of BC in LPG (traditional cookstoves) users households were 3.79 ± 0.77 μgm −3 (25.36 ± 5.01 μgm −3 ) during the winter; 2.62 ± 0.60 μgm −3 (16.36 ± 3.68 μgm −3 ) during the pre-monsoon; 2.02 ± 0.355 μgm −3 (8.92 ± 1.98 μgm −3 ) during the monsoon and 2.19 ± 0.47 μgm −3 (15.17 ± 3.31 μgm −3 ) during the post-monsoon seasons. However, the outdoor BC concentrations were 24.20 ± 4.46, 19.80 ± 4.34, 8.87 ± 1.83, and 9.14 ± 1.84 μgm −3 during winter, pre-monsoon, monsoon and post-monsoon seasons respectively. The negative radiative forcing (RF) at the surface suggests a cooling effect while a warming effect appears to be occurring at the top of the atmosphere. The atmospheric forcing of BC and aerosols also show a net warming effect in the selected study areas. The analysis of BC concentrations and fire episodes indicated that the emissions from biomass burning increases the pollution concentration. The backward trajectory analysis through the HYSPLIT model also suggests an additional source of pollutants during winter and pre-monsoon seasons from the northwest and northern region in the IGP. Graphical abstract: Image 1 Highlights: BC concentrations in LPG user's households was 90.3% lower than biofuels user's families. Both ATM and TOA positive radiative forcing of BC and aerosol particles are showing a net warming effect on the study area while the SUR radiative forcing shows chilling effect. HYSPLIT modeling suggest that the smoke from biomass burning contribute significantly to air pollution levels in the cities.